2013
DOI: 10.13005/bbra/1147
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Salivary Sialic Acid in Patients With Different Clinico-Pathological Stages of Oral Leukoplakia and Oral Squamous Cell Carcinoma - A Cross Sectional Study

Abstract: Early detection of oral cancer is significantly potential with noninvasive methods like salivary analysis which is of utmost importance to reduce the risk rate of advanced stage.As there is paucity in studies performing clinicopathological staging and grading of precancerous and cancerous conditions, this study prompted us to evaluate salivary sialic acid in patients with different clinico pathological stages of oral leukoplakia and oral squamous cell carcinoma in order to develop cost effective,simple diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…[23,24] Hemalatha et al evaluated salivary sialic acid in patients with different clinicopathological stages of OL and OSCC and reported that there was significant increase in the levels of the sialic acid (free and protein bound) levels in patients with OSCC and patients with OL. [25] Similarly, Vajaria et al reported on salivary sialylation changes where the levels of sialic acid were increased in precancerous and oral cancer. [26] Sanjay et al reported a higher level of salivary total protein, total sugar, and sialic acid in OSCC when compared to normal healthy individuals.…”
Section: Discussionmentioning
confidence: 95%
“…[23,24] Hemalatha et al evaluated salivary sialic acid in patients with different clinicopathological stages of OL and OSCC and reported that there was significant increase in the levels of the sialic acid (free and protein bound) levels in patients with OSCC and patients with OL. [25] Similarly, Vajaria et al reported on salivary sialylation changes where the levels of sialic acid were increased in precancerous and oral cancer. [26] Sanjay et al reported a higher level of salivary total protein, total sugar, and sialic acid in OSCC when compared to normal healthy individuals.…”
Section: Discussionmentioning
confidence: 95%
“…Achalli et al showed that the mean serum and salivary sialic acid levels were significantly increased in people with oral premalignant lesions and oral cancer than in healthy controls (39). Hemalatha et al reported that salivary Sialic acid (free & protein-bound) levels were significantly raised in OSCC patients and individuals with oral leukoplakia compared to control groups (40).…”
Section: Glycosylation Related Moleculesmentioning
confidence: 99%